High PTGS2 expression in post‐neoadjuvant chemotherapy‐treated oesophageal adenocarcinoma is associated with improved survival: a population‐based cohort study. Issue 4 (25th January 2019) - Spence, Andrew D; Trainor, James; McMenamin, Úna; Turkington, Richard C; McQuaid, Stephen; Bingham, Victoria; James, Jacqueline; Salto‐Tellez, Manuel; McManus, Damian T; Johnston, Brian T; Cardwell, Chris R; Coleman, Helen G
Abstract : Aims: High prostaglandin endoperoxide synthase‐2 (PTGS2) enzyme expression in oesophageal adenocarcinoma has been shown to independently predict poor prognosis; however, the evidence is inconsistent. The aim of this study was to investigated the association between PTGS2 expression and prognosis in patients with oesophageal adenocarcinoma. Methods and results: A cohort of 135 patients with oesophageal adenocarcinoma who received neoadjuvant chemotherapy and surgery from 2004 to 2012 was identified in the Northern Ireland Cancer Centre. Tissue microarrays were created in the Northern Ireland Biobank, with triplicate cores being sampled from each tumour. Immunohistochemical PTGS2 expression was scored by two independent assessors, with intensity and proportion of tumour staining being used to calculate H‐scores for each patient. Cox regression models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for overall and cancer‐specific survival, and recurrence‐free survival by PTGS2 expression, with adjustment for potential confounders. Patients were followed up for a mean of 3.0 years (standard deviation 1.8 years). The PTGS2 expression cut‐off value was determined from the median H‐score of the cohort (270/300). High ( n = 79), as compared with low ( n = 56), PTGS2 expression was associated with improved cancer‐specific survival (adjusted HR 0.56, 95% CI 0.33–0.94; P = 0.03). PTGS2 expression was not significantly associated with recurrence‐free survival (adjusted HR 0.85, 95% CI 0.52–1.38; P = 0.51). Conclusions: High PTGS2 expression in oesophageal adenocarcinoma tissue was associated with improved overall and cancer‐specific survival, in contrast to previous evidence. As this is the first study of its kind to include patients who had undergone neoadjuvant chemotherapy, further studies are needed to clarify these associations.